QUALITATIVE ANALYSIS OF MEASURED FISH CAPTURE POLICY IN INDONESIA’S FISHERIES MANAGEMENT - Riadi, Septa; Damar, Ario; Purnamadewi, Yeti Lis; Pertiwi, Setyo; Wahyudin, Yudi (Politeknik Kelautan dan Perikanan Dumai, 2024)
Abstract